Efectos de un programa de estrategias comunicativas para estimular el lenguaje oral en preescolares de cinco años - Callao - Cárdenas Pérez, Carmen Udelia (2012)
The present research was to determine the effectiveness of a program of communication strategies in oral language of students 5 years of an educational institution of Callao. The sample consisted of 48 students: of these, 24 make up the control group and the other 24 make up the experimental group to whom the program was applied communication strategies. The instrument used was the oral language test for children 5 years, adapted from ELO (Ramos and others 2008) by Cardenas and Neyra (2011). The purpose of the test was to evaluate the relevant aspects of oral language in its different dimensions: auditory discrimination, phonological, syntactic and semantic. The results revealed that there are significant differences in favor and spoken language among the students who received the program and communication strategies that did not. It was concluded that the program was effective.